uBuntu and certainty in commercial contracting: A study of burial societies in Cape Town - Mzezewa, Sinikiwe (Department of Commercial Law, 2025)
Burial societies are some of the oldest forms of mutual rotating savings groups (stokvels) used to finance funerals in indigenous communities. The parties agree to make monetary and non monetary contributions in exchange for assistance upon death or bereavement of their families. They were formed to mitigate costs associated with upholding the cultural significance of burials in indigenous communities. As such, burial societies are not mere savings clubs but also strengthen social bonds that are critical in communities marred by unemployment and sporadic incomes. These environments require ingenious ways to make ends meet. Despite several products offered by the markets to finance funerals in South Africa, burial societies are relevant and constant in indigenous communities. The underlying agreements between the parties govern their relationships. The agreements are open such that they can easily vary to meet changes in the circumstances of the parties. Their dispute-resolution mechanisms are based on the notion of ubuntu. Given the nature of burial societies, this thesis investigates whether their underlying agreements are certain and enforceable. This requires an in-depth understanding of the contracting practices of burial societies. The law perceives the underlying agreements of burial societies as funeral insurance contracts. This categorisation considers burial societies as juristic persons who operate for profit and who offer public funeral insurance products. However, the nature of burial societies shows that burial societies are not juristic persons but aggregations of individuals with common purposes. As such, categorising their contracts as funeral insurance negates the undeniable nature of burial societies. This thesis argues that the nature of burial society contracts makes them living customary contracts. However, utilising the living customary law theory to arrive at this conclusion presents problems because it is fraught with inaccurate, distorted and undeveloped literature. Hence, there was a need to supplement the conventional doctrinal method with the socio-legal method to ascertain the contracting practices of burial societies. In that light, fieldwork conducted in Cape Town showed that to ensure the reliability of their contracts, burial societies use various methods for concluding contracts and resolving disputes. Furthermore, social bonds among the parties, their circumstances, and the long-term nature of the contracts necessitate contractual flexibility. As such, the thesis contributes original ideas and new insights into the existing knowledge of living customary law contracts at a time when it is becoming clear that a decolonised living customary theory that does not conform to European precepts is necessary for the South African context.